PERANCANGAN ULANG PRODUK OS TABLE DENGAN MENGGUNAKAN METODE ANTROPOMETRI - Widodo, Tri; Ferdiansyah, Ismail; Prasetyo, Adi (Journal Industrial Manufacturing, 2021)
The table is a furniture that has a basic surface and legs as a buffer that varies in shape and function. The design of this product is intentionally dedicated to the needs of a table that has a large capacity to store food, drinks, and even other tools. But the dimensions of the OS Table is currently felt not to provide comfort to its users. Therefore, the idea arose to redesign the multifunctional table design (OS Table) to create comfort for its users. This research was conducted using the Anthropometry method. Based on the results of data processing that has been done by collecting anthropometric data, namely Popliteal Height (Tpo), Elbow Length to Hands (Pst), Sitting Elbow Height (Tsd), Coverage of Hands Forward (Jtd) and Length of Hand Range (Prt), then it can be concluded the results of the OS Table redesign by using the 5th percentile for the smallest and the 95th percentile for the largest resulting in the dimensions of the maximum length of the table is 150 cm and the minimum length of the table is 118 cm, the width of the table is 69 cm while the height of the table is 69 cm. This multifunctional table (OS Table) has been redesigned to achieve an ergonomic dimension, thus providing comfort for the user.Keywords: Tables , OS Table, Anthropometry, Ergonomics, Product Design